2018
DOI: 10.1016/j.jgeb.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Screening of plant growth promoting traits in heavy metals resistant bacteria: Prospects in phytoremediation

Abstract: Phytoremediation is considered as a novel environmental friendly technology, which uses plants to remove or immobilize heavy metals. The use of metal-resistant plant growth-promoting bacteria (PGPB) constitutes an important technology for enhancing biomass production as well as tolerance of the plants to heavy metals. In this study, we isolated twenty seven (NF1-NF27) chromium resistant bacteria. The bacteria were tested for heavy metals (Cr, Zn, Cu, Ni, Pb and Co) resistance, Cr(VI) reduction and PGPB charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(44 citation statements)
references
References 63 publications
1
37
0
2
Order By: Relevance
“…All novel strains were able to produce siderophores, but strain DCY119 T was the strongest producer among the tested strains. Previous studies have demonstrated that the siderophores production activity of strains is directly correlated with enhanced HM resistance and indirectly promotion of plant growth by IAA production ability against HM toxicity [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…All novel strains were able to produce siderophores, but strain DCY119 T was the strongest producer among the tested strains. Previous studies have demonstrated that the siderophores production activity of strains is directly correlated with enhanced HM resistance and indirectly promotion of plant growth by IAA production ability against HM toxicity [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…PGPB enhance the growth of plants through various plant growth-promoting (PGP) traits (e.g., phosphate solubilization, production of indole-3-acetic acid, siderophores, ammonia, hydrogen cyanide and nitrogen fixation) [3][4][5][6]. In addition, they have the potential for metal detoxification and mitigation of plant's stress in polluted environment.…”
Section: Introductionmentioning
confidence: 99%
“…The associated microbes can enhance host plant growth, increase solubility and bioavailability of contaminant and alter heavy metal accumulation through IAA, siderophores, organic acids and biosurfactant production (Li et al ., 2012a; Ullah et al ., 2015a,b; Tirry et al ., 2018). Moreover, microbes can indirectly enhance phytoremediation by stimulating soil microbial communities (Burges et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%